Relevansi Materi Ajar Teks Sastra pada Buku Siswa Bahasa Indonesia SMA dengan Kompetensi Dasar dan Pendekatan Saintifik - Astuti, Chrismeina Tulus; , Dra. Main Sufanti, M.Hum (2016)
Abstract The aimed of this study are describing (1) literature text contained on students' book Indonesian of XI grade SMA (2) relevance of literature teaching materials on students' book Indonesian of XI grade SMA based basic competence, (3) relevance of literature teaching materials on students' book Indonesian of XI grade SMA based scientific approach. This study is a descriptive qualitative research. The data in this study is a word, phrase, sentence, and discourse as well as the table that is a literary teaching material on students' book Indonesian of XI grade SMA. Sources of data in this study guide Ekspresi Diri dan Akademik of XI grade SMA Curriculum 2013. T he data was validated by triangulation technique theory. Data analysis technique used is content analysis and comparison. The results of this study were (1) the type of literature contained on student' book Indonesian of XI grade SMA is short stories, rhymes, poems, couplets, poutry, and review stories. (2) literature teaching material contained on strudents' book have relevant to the basic competencies curriculum in 2013 (3) literature teaching material contained on strudents' book have relevant to scientific approach, is questioning skills.